Health-related physical fitness and physical activity in Portuguese adolescents - Pinto, Joana Batista de Castro (2015)
Introduction: Physiotherapy develops, maintains or restores movement and function, thus maintaining people physically active and with adequate physical condition is one of its main objectives. Therefore, normative values are necessary for the various components of health-‐related physical fitness (HRPF), for the correct prescription of exercise in healthy or not healthy populations. Objective: To contribute to the establishment of normative values of the measures most commonly used in physiotherapy to assess HRPF in Portuguese adolescents, examining gender-‐specific differences and the relationship between HRPF and physical activity (PA). Methods: A cross-‐sectional study was conducted. Socio-‐demographic, anthropometric data and vital signs were collected in adolescents (12-‐17 years old). Their PA levels were assessed using the "Physical Activity Index" (PAI). HRPF was assessed through: body mass index (BMI), incremental shuttle walk test (ISWT), hand-‐held dynamometry (HHD), modified sit-‐and-‐reach test (MSRT) and timed up and go (TUG). Results: One hundred and forty one adolescents participated (71 males). The mean and its 95% confidence intervals obtained for each test were: BMI 58.95 [54.12 – 63.77] percentile; ISWT 1251.19 [1199.25 – 1303.13] meters; HHD 21.04 [19.67 – 22.41] Kilograms; MSRT 38.09 [34.58 – 41.60] centimeters; TUG 4.31 [4.05 – 4.58] seconds. Male adolescents presented better performance in HRPF tests than females, except for BMI. Adolescents had moderate PA levels and, the higher these levels, the better were the results in three of the HRPF tests (ISWT; MSRT; TUG). Conclusion: Findings are a contribution to the development of normative values for HRPF tests in Portuguese adolescents. Higher levels of PA were associated with better HRPF results.